A Method to Combine Neurofilament Light Measurements From Blood Serum and Plasma in Clinical and Population-Based Studies - Rübsamen, Nicole; Willemse, Eline A. J.; Leppert, David; Wiendl, Heinz; Nauck, Matthias; Karch, André; Kuhle, Jens; Berger, Klaus (Frontiers in Neurology, 2022)
Introduction: Neurofilament light (NfL) can be detected in blood of healthy individuals and at elevated levels in those with different neurological diseases. We investigated if the choice of biological matrix can affect results when using NfL as biomarker in epidemiological studies. Method: We obtained paired serum and EDTA-plasma samples of 299 individuals aged 37–67 years (BiDirect study) and serum samples of 373 individuals aged 65–83 years (MEMO study). In BiDirect, Passing–Bablok analyses were performed to assess proportional and systematic differences between biological matrices. Associations between serum or EDTA-plasma NfL and renal function (serum creatinine, serum cystatin C, glomerular filtration rate, and kidney disease) were investigated using linear or logistic regression, respectively. All regression coefficients were estimated 1) per one ng/L increase and 2) per one standard deviation increase (standardization using z-scores). In MEMO, regression coefficients were estimated 1) per one ng/L increase of serum or calculated EDTA-plasma NfL and 2) per one standard deviation increase providing a comparison to the results from BiDirect. Results: We found proportional and systematic differences between paired NfL measurements in BiDirect, i.e. serum NfL [ng/L] = −0.33 [ng/L] + 1.11 × EDTA-plasma NfL [ng/L]. Linear regression coefficients for the associations between NfL and renal function did not vary between the different NfL measurements. In MEMO, one standard deviation increase in serum NfL was associated with greater changes in the outcomes than in BiDirect. Conclusion: Although there are differences between serum and EDTA-plasma NfL, results can be used interchangeably if standardized values are used.